2014
DOI: 10.1186/1129-2377-15-69
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition intervention for migraine: a randomized crossover trial

Abstract: BackgroundLimited evidence suggests that dietary interventions may offer a promising approach for migraine. The purpose of this study was to determine the effects of a low-fat plant-based diet intervention on migraine severity and frequency.MethodsForty-two adult migraine sufferers were recruited from the general community in Washington, DC, and divided randomly into two groups. This 36-week crossover study included two treatments: dietary instruction and placebo supplement. Each treatment period was 16 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 27 publications
(37 reference statements)
1
59
0
3
Order By: Relevance
“…Another study by In concordance with the findings reported by Bunner et al in Washington [4]and Ladson et al, in Saint Louis [20]; reported that regular sleep, meals, and exercise; stress reduction can improve migraine severity and frequency.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Another study by In concordance with the findings reported by Bunner et al in Washington [4]and Ladson et al, in Saint Louis [20]; reported that regular sleep, meals, and exercise; stress reduction can improve migraine severity and frequency.…”
Section: Discussionsupporting
confidence: 80%
“…Migraine is a recurrent, severe, and throbbing headache, and recurrent episodic attacks, which have the potential to headaches with moderate to severe pain, often having a unilateral location and pulsating quality, accompanied by nausea, vomiting, photophobia, or phonophobia [4], [5]. The frequency and severity of headaches can progress over months or years to chronic migraine, in which attacks tend to occur for at least 15days in a month [5], [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study lacked a normal diet control group, so it is unclear how big the effect of simply being placed on a diet might have been, especially given the large placebo effect often seen in headache prophylaxis studies [59]. A more recent study using a similar low fat diet approach, failed to find any effect of the diet on the intensity, frequency or duration of migraine headaches [60]. At present, the effect of lowering arachidonic acid intake on migraine headache or rheumatoid arthritis pain appears modest, at best.…”
Section: Can Dietary Restriction Of Arachidonic Acid Alter Chronic Pain?mentioning
confidence: 95%
“…In this study, diet's propensity to induce IgG antibodies was shown to be the key component in deciding the influence of diet migraine episodes. In another study [16] demonstrated that a low-fat, plant based diet can be an effective in controlling migraine frequency and severity. There are several similar studies that explain how migraine patients who are allergic to certain foods are able to control their migraine episodes as well as severity by being mindful of their diet.…”
Section: Role Of Diet In Migraine Treatmentmentioning
confidence: 99%